A dynamic picture of the halolactonization reaction through a combination of ab initio metadynamics and experimental investigations. Issue 22 (5th May 2021) - Van Lommel, Ruben; Bock, Jonathan; Daniliuc, Constantin G.; Hennecke, Ulrich; De Proft, Frank
Abstract : Ab initio dynamics of the halolactonization reaction provide insights into the diastereoselectivity of the reaction. Noncovalent interactions between the substrate, halogen source and solvent are revealed to direct the formation of the syn -product. Abstract : The halolactonization reaction is one of the most common electrophilic addition reactions to alkenes. The mechanism is generally viewed as a two-step pathway, which involves the formation of an ionic intermediate, in most cases a haliranium ion. Recently, an alternative concerted mechanism was proposed, in which the nucleophile of the reaction played a key role in the rate determining step by forming a pre-polarized complex with the alkene. This pathway was coined the nucleophile-assisted alkene activation (NAAA) mechanism. Metadynamics simulations on a series of model halolactonization reactions were used to obtain the full dynamic trajectory from reactant to product and investigate the explicit role of the halogen source and solvent molecules in the mechanism. The results in this work ratify the occasional preference of a concerted mechanism over the classic two-step transformation under specific reaction conditions. Nevertheless, as the stability of both the generated substrate cation and counter-anion increase, a transition towards the classic two-step mechanism was observed. NCI analyses on the transition states revealed that the activating role of the nucleophile is independent of the formation and stability of the intermediate. Additionally, the dynamic insights obtained from the metadynamics simulations and NCI analyses employed in this work, unveiled the presence of syn -directing noncovalent interactions, such as hydrogen bonding, between the alkenoic acid and the halogen source, which rationalized the experimentally observed diastereoselectivities. Explicit noncovalent interactions between the reactants and a protic solvent or basic additive are able to disrupt these syn -directing noncovalent interactions, affecting the diastereoselective outcome of the reaction.